Sistem Informasi Pengusulan Pembuatan Kartu Bagi Pegawai Pada Kantor Badan Kepegawaian Dan Pengembangan SDM Kota Palembang - Marlindawati, Marlindawati; Agustina, Merry (Jurnal Ilmiah Matrik, 2024)
This research produces an information system that can be used in the process of proposing the manufacture of employee cards, wife cards or employee husband cards at the office of the Palembang City Human Resources Development and Personnel Agency. The system is built using PHP (Hypertext Preprocessor) and MySQL programming languages and based on waterfall method for its development process. With this information system, the process of making employee cards, wife cards and employee husband cards can be done more optimally and quickly including the presentation of reports to the head of the office and for employees can be a matter of pride